How Religious Affiliation and Race/Ethnicity Shape Presidential Policy Approval - Taydas, Zeynep (Politics and religion, 2025)
Does religious affiliation affect evaluations of the president’s policy performance? We examine support for President Barack Obama’s handling of seven policy areas using data from the Pew Research Center. We show that the intersection of race/ethnicity and religion drives support for Obama’s policy performance and that religion’s impact transcends that of partisanship. Compared to Black Protestants, Evangelical Protestants, non-Hispanic Catholics, and (to a lesser extent) seculars and mainline Protestants are significantly less approving of Obama’s policy performance. The most striking result in this study concerns the differences between Black Protestants and evangelicals, as the latter group is consistently opposed to Obama’s handling of policy, whether domestic or international. Taken together, our findings reveal that the political significance of religious affiliation on presidential policy approval intersects powerfully with race/ethnicity.